1995
DOI: 10.1042/bj3090689
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression and characterization of active recombinant rat liver carnitine palmitoyltransferase II using baculovirus

Abstract: The cDNA encoding rat liver carnitine palmitoyltransferase II (CPT-II) was heterologously expressed using a recombinant baculovirus/insect cell system. Unlike Escherichia coli, the baculovirus-infected insect cells expressed mostly soluble active recombinant CPT-II (rCPT-II). CPT activity from crude lysates of recombinant baculovirus-infected insect cells was maximal between 50 and 72 h post-infection, with a peak specific activity of 100-200 times that found in the mock- or wild-type-infected control lysates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…CPT2-knockout cells also showed a reduced ability to label acetyl-CoA and palmitate under equivalent conditions, but the decrease was not as pronounced as that observed in the CROT-knockout cell line. Previous studies have shown that CPT2 disfavors short-chain substates ( 20 , 21 ). To assess the role of CPT1 in LAC metabolism, etomoxir, an irreversible inhibitor of CPT1 that also inhibits CROT ( 22 ), was also tested and shown to reduce palmitate labeling ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…CPT2-knockout cells also showed a reduced ability to label acetyl-CoA and palmitate under equivalent conditions, but the decrease was not as pronounced as that observed in the CROT-knockout cell line. Previous studies have shown that CPT2 disfavors short-chain substates ( 20 , 21 ). To assess the role of CPT1 in LAC metabolism, etomoxir, an irreversible inhibitor of CPT1 that also inhibits CROT ( 22 ), was also tested and shown to reduce palmitate labeling ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The elevated ␤ -hydroxybutyrate measured during the day in fed Ad-Acot2 mice suggests that the lower RQ was due, at least in part, to greater hepatic FAO. The liver acyl-carnitine profi le suggests that mitochondrial uptake of FA was increased; the higher levels of long-chain acyl-carnitines may refl ect reversal of CPT2, with reformation of carnitine esters from medium-or long-chain (but not short-chain) acyl-CoAs ( 35,36 ). It should be noted that skeletal muscle Acot2 protein expression was not elevated in Ad-Acot2 mice, suggesting that FA uptake and utilization in skeletal muscle was similar to that for Ad-Ctrl mice; thus skeletal muscle seems unlikely to be a driver of the higher FA utilization in these mice.…”
Section: Overexpressed Acot2 Facilitates Mitochondrial Faomentioning
confidence: 99%
“…β‐OG was identified as competitive inhibitor of rCPT‐2: with octanoyl‐CoA as substrate β‐OG had a K i of 15 mM, which is half the CMC of β‐OG [19,20]. In addition, Johnson et al observed “abnormal non‐saturation kinetics with respect to palmitoyl‐CoA” (presumably due to self‐association of palmitoyl‐CoA at high concentrations) [21]. These observations led us to refrain from determining K i values for inhibitors 1–4.…”
Section: Methodsmentioning
confidence: 99%